Dari Penolak Bala Hingga Pengamen Jalanan: Pergeseran Eksistensi Ondel-Ondel Perspektif Mulla Sadra Dan Baudrillard - Syarifudin Choirul Umam; Halid; Frans Sayogie (Nazharat: Jurnal Kebudayaan, 2025)
Abstract This study represents the researcher's response to the phenomenon of ondel-ondel as street performers. The study aims to examine the existence of ondel-ondel through the lens of both Islamic and Western philosophy. Using a qualitative approach, the method relies on words, phrases, or sentences to build a narrative and is generally applied in case study research. The findings reveal, from the perspective of Islamic philosophy, that the existence of ondel-ondel has undergone a shift and displays a gradation of existence as street buskers. Meanwhile, from a Western philosophical viewpoint, ondel-ondel busking represents hyperreality, as it becomes detached from its original standards and context as part of Betawi art and culture.